Solution Models based on Symmetric and Asymmetric Information - Antuchevi?ien?, Jurgita (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue covers symmetry and asymmetry phenomena occurring in real-life problems. We invited authors to submit their theoretical or experimental research presenting engineering and economic problem solution models dealing with the symmetry or asymmetry of different types of information. The issue gained interest in the research community and received many submissions. After rigorous scientific evaluation by editors and reviewers, nine papers were accepted and published. The authors proposed different MADM and MODM solution models as integrated tools to find a balance between the components of sustainable global development, to find a symmetry axis concerning goals, risks, and constraints to cope with the complicated problems. Most approaches suggested decision models under uncertainty, combining the usual decision-making methods with interval-valued fuzzy or rough sets theory, also Z numbers. The application fields of the proposed models involved both problems of technological sciences and social sciences. The papers cover three essential areas: engineering, economy, and management. We hope that a summary of the Special Issue as provided here will encourage a detailed analysis of the papers included in the Printed Edition.